Docosahexaenoic Acid Induces Expression of NAD(P)H: Quinone Oxidoreductase and Heme Oxygenase-1 through Activation of Nrf2 in Cerulein-Stimulated Pancreatic Acinar Cells - Yu Jin Ahn; Joo Weon Lim; Hyeyoung Kim (Antioxidants, 2020)
Oxidative stress is a major risk factor for acute pancreatitis. Reactive oxygen species (ROS) mediate expression of inflammatory cytokines such as interleukin-6 (IL-6) which reflects the severity of acute pancreatitis. The nuclear factor erythroid-2-related factor 2 (Nrf2) pathway is activated to induce the expression of antioxidant enzymes such as NAD(P)H: quinone oxidoreductase 1 (NQO1) and heme oxygenase-1 (HO-1) as a cytoprotective response to oxidative stress. In addition, binding of Kelch-like ECH-associated protein 1 (Keap1) to Nrf2 promotes degradation of Nrf2. Docosahexaenoic acid (DHA)—an omega-3 fatty acid—exerts anti-inflammatory and antioxidant effects. Oxidized omega-3 fatty acids react with Keap1 to induce Nrf2-regulated gene expression. In this study, we investigated whether DHA reduces ROS levels and inhibits IL-6 expression via Nrf2 signaling in pancreatic acinar (AR42J) cells stimulated with cerulein, as an in vitro model of acute pancreatitis. The cells were pretreated with or without DHA for 1 h and treated with cerulein (10−8 M) for 1 (ROS levels, protein levels of NQO1, HO-1, pNrf2, Nrf2, and Keap1), 6 (IL-6 mRNA expression), and 24 h (IL-6 protein level in the medium). Our results showed that DHA upregulates the expression of NQO1 and HO-1 in cerulein-stimulated AR42J cells by promoting phosphorylation and nuclear translocation of Nrf2. DHA increased interaction between Keap1 and Nrf2 in AR42J cells, which may increase Nrf2 activity by inhibiting Keap1-mediated sequestration of Nrf2. In addition, DHA-induced expression of NQO1 and HO-1 is related to reduction of ROS and IL-6 levels in cerulein-stimulated AR42J cells. In conclusion, DHA inhibits ROS-mediated IL-6 expression by upregulating Nrf2-mediated expression of NQO1 and HO-1 in cerulein-stimulated pancreatic acinar cells. DHA may exert positive modulatory effects on acute pancreatitis by inhibiting oxidative stress and inflammatory cytokine production by activating Nrf2 signaling in pancreatic acinar cells.